Quantification of the Changes in Potent Wine Odorants as Induced by Bunch Rot (Botrytis cinerea) and Powdery Mildew (Erysiphe necator) - Lopez Pinar, Angela; Rauhut, Doris; Ruehl, Ernst; Buettner, Andrea (Frontiers in Chemistry, 2017)
Fungal infections are detrimental for viticulture since they may reduce harvest yield and wine quality. This study aimed to characterize the effects of bunch rot and powdery mildew on wine aroma by quantification of representative aroma compounds using Stable Isotope Dilution Analysis (SIDA). For this purpose, samples affected to a high degree by each fungus were compared with a healthy sample in each case; to this aim, the respective samples were collected and processed applying identical conditions. Thereby, the effects of bunch rot were studied in three different grape varieties: White Riesling, Red Riesling and Gewürztraminer whereas the influence of powdery mildew was studied on the hybrid Gm 8622-3. Analyses revealed that both fungal diseases caused significant changes in the concentration of most target compounds. Thereby, the greatest effects were increases in the concentration of phenylacetic acid, acetic acid and γ-decalactone for both fungi and all grape varieties. Regarding other compounds, however, inconsistent effects of bunch rot were observed for the three varieties studied.